Synchronous and non-synchronous responses of systems with multiple identical nonlinear vibration absorbers. (21st July 2015) - Issa, Jimmy S.; Shaw, Steven W.
Abstract: In this work we investigate the nonlinear dynamic response of systems composed of a primary inertia to which multiple identical vibration absorbers are attached. This problem is motivated by observations of systems of centrifugal pendulum vibration absorbers that are designed to reduce engine order torsional vibrations in rotating systems, but the results are relevant to translational systems as well. In these systems the total absorber mass is split into multiple equal masses for purposes of distribution and/or balance, and it is generally expected that the absorbers will act in unison, corresponding to a synchronous response. In order to capture nonlinear effects of the responses of the absorbers, specifically, their amplitude-dependent frequency, we consider them to possess nonlinear stiffness. The equations of motion for the system are derived and it is shown how one can uncouple the equations for the absorbers from that for the primary inertia, resulting in a system of identical resonators that are globally coupled. These symmetric equations are scaled for weak nonlinear effects, near resonant forcing, and small damping. The method of averaging is applied, from which steady-state responses and their stability are investigated. The response of systems with two, three, and four absorbers are considered in detail, demonstrating a rich variety of bifurcations of the synchronous response, resulting in responses with various levels of symmetry in which sub-groups of absorbers are mutually synchronous. It is also shown that undamped models with more than two absorbers possess a degenerate response, which is made robust by the addition of damping to the model. Design guidelines are proposed based on the nature of the system response, with the aim of minimizing the acceleration of the primary system. It is shown that the desired absorber parameters are selected so that the system achieves a stable synchronous response which does not undergo jumps via saddle-node bifurcations, nor instabilities related to the underlying symmetry of the system.